Chatbot Artificial Intelligence (AI) to Supporting Differentiated Mathematics Learning - Laja, Yosepha Patricia Wua; Delvion, Eduardus Beo Seso; Siahaan, Meiva Marthaulina Lestari (FKIP Universitas Lampung, 2025)
Artificial Intelligence chatbots have become famous nowadays because of their ease of use, which is even felt by educators and students. However, the AI chatbot algorithm sometimes does not match what is expected because it is not precise and does not match the prompt. For example, when we type the prompt